Diverse functions of miR-125 family in different cell contexts - Sun, Yu-Meng; Lin, Kang-Yu; Chen, Yue-Qin (Journal of hematology and oncology, 2013)
MicroRNAs (miRNAs) are emerging as a novel class of non-coding RNA molecules that regulate gene expression at a post-transcriptional level. More than 1000 miRNAs have been identified in human cells to date, and they are reported to play important roles in normal cell homeostasis, cell metastasis and disease pathogensis and progression. MiR-125, which is a highly conserved miRNA throughout diverse species from nematode to humans, consists of three homologs hsa-miR-125a, hsa-miR-125b-1 and hsa-miR-125-2. Members of this family have been validated to be down-regulated, exhibiting its disease-suppressing properties in many different types of diseases, while they also have disease-promoting functions in certain contexts. MiR-125 targets a number of genes such as transcription factors, matrix-metalloprotease, members of Bcl-2 family and others, aberrance of which may lead to abnormal proliferation, metastasis and invasion of cells, even carcinomas. Furthermore, miR-125 plays a crucial role in immunological host defense, especially in response to bacterial or viral infections. In this review, we summarize the implication of miR-125 family in disease suppression and promotion, focusing on carcinoma and host immune responses. We also discussed the potential of this miRNA family as promising biomarkers and therapeutic targets for different diseases in future.